Measurement of User Satisfaction of ELSIMIL Application in Stunting Prevention in Indonesia using EUCS Method - Zacky, M.; Saputra, Eki (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Stunting is a long-term nutritional problem diagnosed in children under two years old and characterized by shorter height difference compared to children of the same age. A public health concern, stunting increases a child's risk of illness and death and stunts their ability to thrive intellectually and physically. The government has given primary responsibility for preventing stunting to the National Population and Family Planning Agency (BKKBN). One of BKKBN's efforts is to develop the ELSIMIL application, which is a media application for screening, mentoring and preventing stunting. However, during the implementation of the use of the ELSIMIL application, there are many problems faced by the family assistance team and prospective brides, one of which is the lack of knowledge of prospective brides in running the ELSIMIL application, for example: during the registration of bride and groom data, there are still many errors in inputting data so that the results issued in the form of an ELSIMIL certificate do not match the condition of the prospective bride and groom. This study uses the End-User Computing Satisfaction (EUCS) method to assess user satisfaction in running the ELSIMIL application. This study shows that the content variable has a significant influence on user satisfaction compared to other variables such as accuracy, format, ease of use, and timeliness. The more relevant and quality information is presented, the more satisfied users will be. However, simultaneously all variables affect user satisfaction. The implications of these findings can provide valuable guidance for digital platform developers and related parties in designing more targeted and effective interventions, as well as facilitating desired behavioral changes in society.